The Impacts and Problem Solving Guidelines on Non-registered Population of Local Administrative Organization: A Case Study of Theppharat Sub-district Municipality, Ban Pho District, Chachoengsao Province - Sintarako, Atipat; Chaiyarit, Atiyaphorn; Khunkha, Nopporn (Ratchaphruek Journal, 2020)
The objectives of this research project were aimed to 1) analyze the impacts of non-registered population, 2) analyze the impacts of problems on non-registered population towards public service, and 3) study the solving guidelines on the impacts of problems caused by non-registered population of Theppharat Sub-district Municipality, Ban Pho District, Chachoengsao Province. The present research was qualitative research. There were 15 key informants: Mayor, Deputy Mayor, Municipal Clerk, Chief Section of Policy and Planning, community leaders and local people. The findings revealed that the impacts of problem on the non-registered population were found in following: 1) Economic aspect, the non-registered population had improved the economic condition,2) Social aspect, the social structure had changed in the community population and increased the problem on wastes, 3) Cultural aspect, the non-registered population did not affect the community culture condition, and 4) Security aspect, the crime problem impacted the non-registered population. Concerning the problem caused by non-registered population towards public service, it was found that there were two points: Waste management and Educational service. Incidentally, the problem-solving guidelines relied on the effective management, sustainable solving problem and cultivation of awareness among people in the community. On the other hand, the community needs to set the rules and regulation, limitation of budget, and incomplete guidelines of waste management.